An Influence of Social and Legal Context on family formation in Thai society: A Comparative study on Thai-Buddhist and Thai-Muslim Family - Senkhaw, Pakapon; Emraja, Chatchai (Nitipat NIDA Law Journal, 2026)
The research article titled “Influences of social and legal context on family formation in Thai society: A comparative study on Thai-Buddhist and Thai-Muslim family” examines the family formation process according to Islamic principles, compared to the family formation process in Thai society. The research method involves in-depth interviewed with members of two selected families for comparison between Thai Buddhist and the devout Muslim family. Both families have children who are in the working age. The research results indicate differences in family formation between Buddhist and Muslim groups, based on case studies employed in this study. In Thailand since the Civil and Commercial Code and the philosophy of Buddhism provide freedom and equality for choosing spouses even though there is the principle for maintaining a family, it is only a principle for maintaining a long-lasting married life, whereas Islamic law clearly defines the penalties. According to Sharia law, engaging in sexual relations outside of marriage constitutes a criminal offense that carries specific legal punishments. Furthermore, if the offender does not receive punishment in this world, it is believed that they will be held accountable and punished on the day of judgment. The Quran also provides the strict rules and guidelines for marriage and spouse selection that directly affect the formation of family among the Muslim population.